Assessment of prevalence and causative factors for replacement of composite and amalgam restorations: An observational study - Rahaf Naseer Alhoshani; Asma Munir Khan (Wolters Kluwer Medknow Publications, 2024)
Aim: This study intends to evaluate the frequency and causes of replacement for failed amalgam and composite dental restorations. Methodology: A cross-sectional study comprising female patients with failed permanent composite and amalgam restorations aged 15-60 years old was carried out at the dental clinics of Qassim University. Using a self-structured proforma, demographic data and causes for restoration failure were recorded. The effectiveness of the restorations was assessed by using the Ryge criteria after performing clinical and radiographic examinations. The Statistical Package for Social Science was used for the statistical analysis. Results: It is found that 84.6% of the 299 unsuccessful restorations examined were composite, and 15.4% were amalgam. The main reason for dental failure for both amalgam (95.6%) and composite (93.28%) restorations was secondary caries. Failure of amalgam restoration was largely caused by poor marginal adaptation. With varied incidences between amalgam and composite restorations, typical complaints included discomfort, sensitivity, pain, and food impaction with soreness. The main justification for replacement in amalgam restorations was sensitivity. Repair and replacement rates were similar for amalgam, composite, and mandibular/maxillary restorations. Moreover, 21.1% of individuals overall reported no symptoms, with 8.7% in the amalgam group and 23.3% in the composite group with significant differences (χ2 = 34.28, P = 0.001). Conclusion: According to the current study, secondary caries was found to be the main reason for both amalgam and composite restoration failure. The main problems reported were sensitivity, discomfort, and pain with amalgam showing more sensitivity-related failures.